2013
DOI: 10.1371/journal.pone.0068646
|View full text |Cite
|
Sign up to set email alerts
|

High and Distinct Range-Edge Genetic Diversity despite Local Bottlenecks

Abstract: The genetic consequences of living on the edge of distributional ranges have been the subject of a largely unresolved debate. Populations occurring along persistent low latitude ranges (rear-edge) are expected to retain high and unique genetic diversity. In contrast, currently less favourable environmental conditions limiting population size at such range-edges may have caused genetic erosion that prevails over past historical effects, with potential consequences on reducing future adaptive capacity. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 85 publications
6
80
0
Order By: Relevance
“…Latitudinal gradients in air and sea temperatures, which are intensified by upwelling events that dominate north-western Iberia during summer periods (Ar ıstegui et al 2006), have been reported as the cause of species' distributional patterns. In particular, the western Iberian coastline studied here represents latitudinal clines in abundance and distributional edge limits for many coastal species (Boaventura et al 2002, Pereira et al 2006, Assis et al 2013.…”
Section: Demographic Life-history and Morphological Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Latitudinal gradients in air and sea temperatures, which are intensified by upwelling events that dominate north-western Iberia during summer periods (Ar ıstegui et al 2006), have been reported as the cause of species' distributional patterns. In particular, the western Iberian coastline studied here represents latitudinal clines in abundance and distributional edge limits for many coastal species (Boaventura et al 2002, Pereira et al 2006, Assis et al 2013.…”
Section: Demographic Life-history and Morphological Variablesmentioning
confidence: 99%
“…Abundance patterns, and demographic parameters in general, appear to be driven by interacting fluctuations of several environmental factors and are more variable than originally thought (e.g., Gaston 2009, Viejo et al 2010. Relative to the core, southern edge populations of many species show lower intrapopulation genetic diversity and increased interpopulation genetic divergence due to habitat fragmentation, increased random genetic drift, bottleneck effects, and reduced gene flow (Arnaud-Haond et al 2006, Provan and Maggs 2011, Assis et al 2013. However, there is increasing doubt as to the generality of this correlation (reviewed in Eckert et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrasting patterns at the northern and southern range peripheries for temperate species may not be surprising given the vastly different environmental conditions organisms are likely to experience (e.g. Hoban et al 2010, Assis et al 2013, Hasselman et al 2013). However for a tropical species such as the neon damselfish we expected similar genetic patterns as, presumably, individuals experience similar environmental conditions at both latitudinal range peripheries.…”
Section: Contrasting Patterns In the Northern And Southern Peripherymentioning
confidence: 99%